Evaluation and comparison of the potential of two ferritins as anti-tick vaccines against Haemaphysalis longicornis - Galay, Remil Linggatong; Miyata, Takeshi; Umemiya-Shirafuji, Rika; Maeda, Hiroki; Kusakisako, Kodai; Tsuji, Naotoshi; Mochizuki, Masami; Fujisaki, Kozo; Tanaka, Tetsuya (Parasites & vectors, 2014)
BACKGROUND: Tick control is an essential aspect of controlling the spread of tick-borne diseases affecting humans and animals, but it presently faces several challenges. Development of an anti-tick vaccine is aimed at designing cost-effective and environmentally friendly protection against ticks and tick-borne diseases as an alternative to the use of chemical acaricides. A single vaccine from the tick midgut protein Bm86 is currently available for field applications, but its efficacy is limited to only some tick species. Identification of candidate vaccine antigens that can affect multiple tick species is highly desirable. The hard tick Haemaphysalis longicornis has two kinds of the iron-binding protein ferritin (HlFER), an intracellular HlFER1 and a secretory HlFER2, and RNA interference experiments showed that these are physiologically important in blood feeding and reproduction and in protection against oxidative stress. Here we investigated the potential of targeting HlFERs for tick control by immunizing the host with recombinant HlFERs (rHlFER1 and rHlFER2). METHODS: Rabbits were immunized with rHlFERs three times subcutaneously at two-week intervals. Antisera were collected before the first immunization and a week after each immunization to confirm the antigen-specific serum antibody titer by serum ELISA. Two weeks after the final immunization, the rabbits were challenged with tick infestation. After dropping, tick feeding and reproduction parameters were evaluated to determine vaccine efficacy. To demonstrate the effects of antibodies, oxidative stress was detected in the eggs and larvae. RESULTS: The antibody titer of rHlFER-immunized rabbits greatly increased after the second immunization. Antibodies exhibited cross-reactivity with rHlFERs and reacted with tick native HlFERs in Western blot analysis. Significantly lower bodyweight was observed in the ticks infested from the rHlFER2-immunized rabbit compared to those from the control rabbit. Reduced oviposition and hatching rate were observed in both rHlFER-immunized groups. rHlFER2 showed a higher vaccine efficacy. The antibodies against rHlFERs were detected in the eggs, and higher levels of oxidative stress biomarkers in the eggs and larvae, of ticks from rHlFER vaccinated rabbits. CONCLUSION: Collectively, these results showed that HlFER2 has a good potential as an anti-tick vaccine antigen that may affect multiple tick species.